2022
DOI: 10.1002/ijc.33991
|View full text |Cite
|
Sign up to set email alerts
|

Gene signature of circulating platelet‐bound neutrophils is associated with poor prognosis in cancer patients

Abstract: Main text Novelty and ImpactPlatelets physically interact with peripheral blood neutrophils to form neutrophil-platelet aggregates (NPAs), known to promote disease worsening in various inflammatory diseases. However, characterization of NPAs in cancer remains totally unexplored. We showed that NPAs-associated neutrophils were a yetunreported unique subset of circulating neutrophils associated with a worse patient prognosis in several cancer types. NPAs may hold clinical utility as novel non-invasive blood prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Interestingly, such a group of IFN‐stimulated TANs has also been identified in LC 74 and pancreatic cancer, 72 suggesting the conserved neutrophil subtypes in different disease conditions. Besides, Lecot et al 76 . reported that a subgroup of peripheral neutrophils that bind to neutrophil–platelet aggregates hold a higher capacity for chemotaxis and trans‐endothelial migration, which predicts dismal prognosis in solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, such a group of IFN‐stimulated TANs has also been identified in LC 74 and pancreatic cancer, 72 suggesting the conserved neutrophil subtypes in different disease conditions. Besides, Lecot et al 76 . reported that a subgroup of peripheral neutrophils that bind to neutrophil–platelet aggregates hold a higher capacity for chemotaxis and trans‐endothelial migration, which predicts dismal prognosis in solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is commonly found in several pathological disease states, such as severe infection, hyperimmunoglobulinemia, autoimmune diseases, and malignant tumors. [3][4][5][6] Leucoagglutination mostly involves neutrophils, resulting in pseudoneutropenia, then followed the lymphoagglutination and monocyte aggregation. 7 Hereditary elliptocytosis (HE) is one of the most common red cell membrane disorders, caused by a number of different gene mutations.…”
Section: E T T E R T O T H E E D I T O R Edta-dependent Leucoagglutin...mentioning
confidence: 99%
“…Specific mechanisms are associated with tumor cell proliferation, apoptosis, and the immune microenvironment 240,241 . As study advances, researchers have shown that neutrophils undergo phenotype and functional remodulation under the influence of tumors and their microenvironment, playing a complicated role in tumor development and metastasis 242–244 . Besides protumor activity through protumor neutrophils, NETs, and various subsets associated with cancer process, neutrophils also exert antitumor functions via antitumor neutrophils, other derivatives, and subsets inhibiting cancer process (Figure 5).…”
Section: Neutrophil Heterogeneity In Diseasesmentioning
confidence: 99%